A Preliminary Study of Aphrodisiac Property from Porcupine Tail Meat Ethanol Extract in Male Mice - Anita, Syahfitri; Agusta, Andria; Farida, Wartika Rosa; Nugroho, Herjuno Ari; Wulansari, Dewi (Masyarakat Zoologi Indonesia, 2017)
This study aim to examine the aphrodisiac activity of ethanol extract from the tail meat of porcupine (Hystrix javanica F. Cuvier, 1823) that is traditionally believed by people in Java (Indonesia) could enhance male vitality and sexual perfor-mance. Twenty sexually inexperienced male mice were randomly divided into four groups and paired with artificially estrus female mice after one hour of drug an extract administration. Two doses of ethanol extract; 150 and 750 mg/kg were administered (p.o) to male mice. Sildenafil citrate was used as the positive control while 5% Tween 80 solution used as the negative control. Sexual behavior parameters such as mounting and intromission were observed for three hours of mating. Male mice treated with ethanol extract of porcupine tail meat at the dose 750 mg/kg BW showed higher mounting and intromission frequency compared to the group of ethanol extract dose 150 mg/kg. After 2 hours of admin-istration showed the highest frequency compared to all groups. However, the ethanol extract could not reduce the mount-ing and intromission latency as low as sildenafil citrated treated group. Present findings provide preliminary evidence of aphrodisiac properties from the ethanol extract of porcupine tail meat.